Parasagittal Falcine-Sagittal Sinus Angle Meningioma of the Left Frontal Lobe of the Brain (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The use of high-tech microsurgical techniques in operating on patients with extracerebral intracranial tumors has increased the degree of radicality of the intervention, reduced the incidence of relapses, shortened the length of hospital stay after surgery, and decreased the incidence of postoperative complications and deaths [1–3]. However, disability in patients after meningioma removal reaches 28.8–47.5% [4]. This justifies the need for an in-depth study of the mechanisms of development of clinical manifestations of the disease in patients operated on for a brain tumor using modern techniques. Meningiomas are the most common benign tumors of the central nervous system, originating from the arachnoid cells of the arachnoid membrane. Parasagittal and falx meningiomas account for approximately 25% of all intracranial meningiomas and present significant surgical complexity due to their proximity to the superior sagittal sinus. Total resection (Simpson I) in such cases is the optimal strategy, ensuring a minimal risk of recurrence.